The Influence of Organizational Culture, Leadership Style, and Remuneration on Improving Employee Performance At The Regional Office of The Directorate General of Customs and Excise (DJBC) Banten - Abdul Latif; Jefirstson R Riwu Kore (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to analyze and prove the influence of organizational culture, leadership style, and remuneration on improving employee performance at the Regional Office of the Directorate General of Customs and Excise (DJBC) Banten. The method used in this study is a quantitative descriptive research method, data collection using a questionnaire. The sampling technique uses saturated samples, namely taking the entire population of 131 respondents. The data analysis method used is multiple linear regression—data processing using SPSS 26 analysis tools. The results of partial data testing using the t-test show that organizational culture has a positive effect on employee performance with a significant value of 0.000 <0.050, leadership style has a positive effect on employee performance with a significant value of 0.032 <0.050. Remuneration has a positive effect on employee performance, with a significant value of 0.048 <0.050. The results of the F test show a positive and significant influence between the variables of organizational culture, leadership style, and remuneration on the performance of employees of the Regional Office of the Directorate General of Customs and Excise (DJBC) Banten. This is based on the results of the F test, which obtained the Fcount value of 47.18 and Ftable of 2.60. The size of the contribution contributed by the influence of organizational culture variables, leadership style, and remuneration can be seen in the R Square value of 0.527, which means that the influence of these three variables simultaneously on employee performance variables is 52% and 48% is influenced by other factors which were not examined in this study.